2018
DOI: 10.1021/acs.jnatprod.8b00215
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Violaceoid A and (−)- and (+)-Violaceoid B

Abstract: The first total synthesis of violaceoid A, a cytotoxic agent, and the asymmetric total synthesis of (−)-and (+)-violaceoid B are reported. The precursor was accessed by desymmetrization of a substituted quinol moiety, and the racemic secondary alcohol was kinetically resolved using a chiral nucleophilic catalyst. The asymmetric synthesis of (−)-and (+)-violaceoid B elucidated the absolute configuration of the naturally occurring violaceoid B. Synthetic violaceoid A inhibited the growth of human breast cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The synthesis of aldehyde 5, as outlined in Scheme 1, began with the direct transformation of dinitrile 6 to diester 7, [7] achieving a yield of 52%. This yield is comparable to the combined yield of the hydrolysis and esterification steps in our prior work, [3] effectively eliminatiing one step in the process. Subsequently, the hydroxy groups of the ester were protected using tertbutyldiphenylsilyl (TBDPS) group, resulting in protected ether 8.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The synthesis of aldehyde 5, as outlined in Scheme 1, began with the direct transformation of dinitrile 6 to diester 7, [7] achieving a yield of 52%. This yield is comparable to the combined yield of the hydrolysis and esterification steps in our prior work, [3] effectively eliminatiing one step in the process. Subsequently, the hydroxy groups of the ester were protected using tertbutyldiphenylsilyl (TBDPS) group, resulting in protected ether 8.…”
Section: Resultssupporting
confidence: 62%
“…We previously reported the first total synthesis of violaceoid A and violaceoid B in 2018. [3] Recently, in 2021, Narita, Watanabe and coworkers reported the concise total synthesis of violaceoid A (1) and the first total synthesis of violaceoid C (3). [4] Followin these development, we achieved the first total synthesis of eutyscoparol A (4) and total synthesis of violaceoid C (3).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the first total syntheses of violaceoid A and violaceoid B in 2018. [4] Recently, in 2021, Narita, Watanabe and co-workers reported the concise total synthesis of violaceoid A (1) and the first total synthesis of violaceoid C (3). [5] As another efficient synthesis of 1, Matsushima and coworkers reported the simple total synthesis of 1 via 4.…”
Section: Introductionmentioning
confidence: 99%
“…The first total syntheses of 1 and 2 were performed by Shiina et al in 2018, and the absolute configuration of 2 was established by its synthesis. 7) They utilized 3,6-dihydroxyphthalonitrile as a starting material, and the synthetic route required a relative multistep sequence involving protection-deprotection and oxidation-reduction steps (1: 10 steps, 11% overall yield; 2: 21 steps, including several repetitive kinetic resolutions and acetonide deprotection steps and 1.3% overall yield). In this study, we observed that boronic acid played a dual role, as a protective and coupling reagent, in the Suzuki-Miyaura cross-coupling of 3-bromo-2-(hydroxymethyl)phenol, and a concise synthesis of 1 employing this strategy was described.…”
Section: Introductionmentioning
confidence: 99%